2021
DOI: 10.3390/app112210878
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Detection of Asymptomatic Ganoderma boninense Infection of Oil Palm Seedlings Using NIR-Hyperspectral Data and Support Vector Machine

Abstract: Breeding programs to develop planting materials resistant to G. boninense involve a manual census to monitor the progress of the disease development associated with various treatments. It is prone to error due to a lack of experience and subjective judgements. This study focuses on the early detection of G. boninense infection in the oil palm seedlings using near infra-red (NIR)-hyperspectral data and a support vector machine (SVM). The study aims to use a small number of wavelengths by using 5, 4, 3, 2, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Furthermore, combining spectral features with ML algorithms achieves high levels of accuracy in differentiating the different biotic attacks that plants can suffer [37]. This algorithm showed sensitivity and accuracy in detecting diseases in the early stages of attack, even without a physical signal, and its performance was increased by using hyperspectral data [38]. Additionally, reflectance values across different wavelengths guarantees more information for the algorithms, improving their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, combining spectral features with ML algorithms achieves high levels of accuracy in differentiating the different biotic attacks that plants can suffer [37]. This algorithm showed sensitivity and accuracy in detecting diseases in the early stages of attack, even without a physical signal, and its performance was increased by using hyperspectral data [38]. Additionally, reflectance values across different wavelengths guarantees more information for the algorithms, improving their performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as the degree of correct diagnosis of the category in a total of two categories. This parameter indicates the number of correctly identified patterns and is formulated and defined as follows [50]:…”
Section: Criteria For Model Evaluationmentioning
confidence: 99%
“… Khairunniza-Bejo et al (2021) investigated the possibility of using fewer wavelengths between one and five in order to counter the economic aspect of hardware design. The results were then compared to detection results obtained from vegetation indices developed using spectral reflectance extracted from two wavelengths from the same hyperspectral sensor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In both single-band reflectance and vegetation index datasets, the results showed that a kernel with a simple linear separation between two classes would be more suitable for G. boninense detection than the others. A linear SVM with a single-band reflectance at 934 nm was identified as the best detection model because it was not only cost effective but also demonstrated high accuracy (94.8%), specificity (92.5%) and sensitivity (97.6%) ( Khairunniza-Bejo et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%